Low risk of clinically important central nervous system dysraphism in a cohort study of 69 patients with isolated aplasia cutis congenita of the head. Issue 3 (13th February 2020) - Kuemmet, Travis J.; Miller, James J.; Michalik, Daniel; Lew, Sean M.; Maheshwari, Mohit; Humphrey, Stephen R.
Abstract: Background: Aplasia cutis congenita of the head may be associated with underlying fusion defects in the skin, soft tissues, muscle, or bone. The risk of central nervous system dysraphism in patients with aplasia cutis congenita is not known; however, knowledge of underlying structural defects can inform management considerations. Methods: This retrospective review investigated the risk of cranial central nervous system dysraphism in children presenting with aplasia cutis congenita of the head, who presented between 1/1/2000 and 6/15/2016. Inclusion criteria were subjects with aplasia cutis congenita of the head who received CT or MR imaging of the head. Results: We identified a total of 69 subjects with aplasia cutis congenita affecting the head and who received imaging. The most common location of the aplasia cutis congenita lesion was the vertex scalp (49.3%). The hair collar sign was present in 27.5% of patients. Twelve of 69 patients (17.4%) demonstrated abnormalities of the bone, vasculature, or brain on head imaging. Only one patient had a diagnosis of encephalocele that required neurosurgical intervention. There was a statistical association between the hair collar sign and the presence of abnormal imaging findings ( P = .029), with a negative predictive value of 89.4%. Conclusions: The incidence of central nervous system dysraphism in patients with aplasia cutis congenita of the head appears to be low, and it may not be necessary to image the head of each child presenting with this skin lesion. The hair collar sign may be a marker of underlying defects.